Validation of the neuroconnective endophenotype questionnaire (NEQ): a new clinical tool for medicine and psychiatry resulting from the contribution of Ehlers–Danlos syndrome - Bulbena, Antonio; Rosado, Silvia; Cabaleiro, Marina; Martinez, María; Baeza-Velasco, Carolina; Martin, Luis-Miguel; Batlle, Santiago; Bulbena-Cabré, Andrea (Frontiers in Medicine, 2023)
The link between anxiety disorders and joint hypermobility syndrome (now under the hypermobility spectrum disorders, which include hypermobile Ehlers-Danlos syndrome) has been widely replicated over the past thirty years and has grown beyond the initial nosological limits. To integrate clinical and research progress in this field, a new Neuroconnective Endophenotype (NE) and its corresponding instrument, the Neuroconnective Endophenotype Questionnaire (NEQ) have been developed. This new clinical construct, created with the active participation of patients, includes both somatic and psychological dimensions as well as symptoms and resilience items. The NE includes five dimensions: 1) Sensorial Sensitivity, 2) Body signs and symptoms, 3) Somatic conditions, 4) Polar behavioural strategies, and 5) Psychological and Psychopathological dimensions. The NEQ information is collected through four self-administered questionnaires (sensorial sensitivity, body signs and symptoms, polar behavioural strategies, and psychological characteristics) and a structured diagnostic part that should be completed by a trained subject. This hetero-administered part incorporates, a) psychiatric diagnoses (using structured criteria, e.g., MINI) b) somatic disorders diagnosis, using structured criteria, and c) assessment of joint hypermobility criteria. In a sample of 36 anxiety cases with 36 matched controls, the NEQ obtained high scores for test-retest, inter-rater reliability, and internal consistency. As for predictive validity, cases and controls significantly differed in all five dimensions as well as hypermobility measurements. We can conclude that the NEQ has achieved acceptable reliability and validity values and, therefore, is ready to be used and tested in different samples. This original and consistent construct including somatic and mental items may improve clinical specificity, the search for more comprehensive therapies, as well as their genetic and neuroimaging bases.